Spatial Analysis of Liquid Pollutant Potential in Industrial Type UKL-UPL Documents In Jombang Regency - Naufal Hilmy Amanur Qolby (Universitas Airlangga, 2022)
Background: The establishment of new industries is often associated with potential waste to be produced and environmental problems that may arise due to the activities carried out by the industry in the future. One of many environmental problems due to industrial waste is the pollution of water, air, and soil in the area around where the industry is located. The number of industrial types UKL-UPL submissions in Jombang Regency from 2006-2020 is unstable but tend to increase from 2015-2020. Jombang Regency is a downstream area of the Brantas River which its Water Quality Index has decreased from 49.17 in 2015 to 47.68 in 2016.Objectives: The purpose of this study was to analyze spatially the location of the industry that had the potential for liquid pollutants and river distribution in Jombang Regency.Methods: This study uses observational research design with a quantitative descriptive approach with a spatial analysis model. The data used is secondary data, namely the submission data of Jombang Regency UKL UKL document in 2006-2020, coordinate data of the location of the industry, and spatial river data.Results: Industrial establishment plans on Jombang Regency are mostly centered around it's regency seat. The length of rivers in Jombang tend to be longer in the northen and sourthern sub-districts. There is no significant difference on the location of industrial establishment plan to the nearest river for industries with and without liquid pollutant potentials (0.912 < 0.05).Conclusion: Even thought sub-districts with high industry counts has shorter river length, regular river water quality monitoring is required to be done so that it doesn't exceed environmental quality standards and cause health problems.